Exploring the diversity of tomb typology with accompanied burial practices in its socio-economic contexts in the Wadi Suq period, Southeast Arabia. - Kuronuma, Taichi (Proceedings of the Seminar for Arabian Studies, 2025)
A variety of tomb types for individual and collective burials is a characteristic of the Wadi Suq period (Middle Bronze Age) in Southeast Arabia. Although the tombs and their types have been classified by previous studies, the annually growing number of excavated and surveyed tombs necessitates continuous updates to enhance the understanding of regional aspects of mortuary practices. This paper aims to present the latest overview of regional aspects in mortuary practices and discuss their possible socio-economic contexts through the study of 114 sites with cemeteries extracted from publications and relevant open sources. The results indicate that the socio-economic contexts influenced the establishment of cemeteries and the selection of tomb types and burial practices, and it resultantly affected to the diverse aspects of Wadi Suq mortuary customs. However, at the same time, it is also argued that there is no absolute correspondence between the subsistence strategies of the social groups and the tomb types or burial practices. Although regional tendencies are generally observable, they likely result from a combination of socio-economic, local environmental, and cultural factors. The diversity of mortuary practices reflects the Wadi Suq people’s apt adaption to specific topographical and environmental conditions, grounded in a common ideological foundation.